Efficacy and Tolerability of Latanoprost 0.005% in Treatment of Primary Open Angle Glaucoma (POAG) - Ali Raza, Muhammad Imran Janjua, Saira Bano (Pakistan Journal of Ophthalmology, 2017)
Purpose: Glaucoma is considered as a type of optic neuropathy for which intraocular pressure (IOP) is accepted as an important causative factor. Previous research has emphasized the value of IOP reduction in treatment of glaucoma. There are many treatment modalities available including medical and surgical options. This study was undertaken to show the effectiveness and safety profile of latanoprost 0.005% in reducing the intraocular pressure to acceptable levels. Materials and Methods: This study was carried out at Department of Ophthalmology, Holy Family Hospital, Rawalpindi, from July to December 2015. Fifty patients diagnosed with primary open-angle glaucoma (POAG) were included in the study. Following baseline measurements of IOP, topical latanoprost 0.005% was administered once daily in the evening for 12 weeks. Patients were followed up with visits at two, six and twelve weeks. Mean IOP reduction was taken as the primary parameter. The ocular side effects of the drug were also assessed by patient’s history and slit lamp examination. Results: Fifty patients, 22 (44%) males and 28 (56%) females, were enrolled for the study. The age ranged from 28 to 70 years with a mean of 59.56 (± 9.24) years. The mean IOP at baseline was 22.48 mmHg (± 6.4). The IOP at 2 weeks was 17.72 mmHg (± 4.70), at 6 weeks 14.88 mmHg (± 4.19) and at 12 weeks 13.20 mmHg (± 3.03) showing a mean reduction of 9.28 mmHg (± 5.36) from baseline. There was marked difference (± 41.28%) between the baseline and final IOP readings (p < 0.001). 12 (24%) patients had ocular side effects of medication. The side effects reported were ocular irritation in 8 (16%), conjunctival hyperemia in 2 (4%) and watering of eyes in 2 (4%) patients. None of them required discontinuation of medication. 38 (76%) patients did not develop any side effects. Conclusion: Latanoprost can be regarded as an effective ocular hypotensive drug, having good compliance profile and no serious side effects. Key words: Latanoprost, Primary Open Angle Glaucoma (POAG).